A new generation of antipsychotics: pharmacology and clinical utility of cariprazine in schizophrenia - Caccia S; Invernizzi RW; Nobili A; Pasina L (Dove Medical Press, 2013)
Silvio Caccia, Roberto William Invernizzi, Alessandro Nobili, Luca Pasina IRCCS-Istituto di Ricerche Farmacologiche Mario Negri, Milan, Italy Abstract: Cariprazine is a potential antipsychotic awaiting approval from the US Food and Drug Administration. It is a dopamine D2- and D3-receptor partial agonist, with higher affinity for D3 receptors, as opposed to the D2 antagonism of most older antipsychotic agents. Like most lipophilic antipsychotics, it undergoes extensive hepatic metabolism by cytochrome P450 (CYP), mainly the highly variable 3A4, with the formation of active metabolites. However, the parent compound – particularly its active didesmethyl derivative – is cleared very slowly, with elimination half-lives in schizophrenic patients ranging from 2–5 days for cariprazine to 2–3 weeks for didesmethyl-cariprazine. Exposure to the latter was several times that for cariprazine, although didesmethyl-cariprazine did not reach steady state within the 3 weeks of 12.5 mg/day dosing. Preliminary information on its therapeutic role comes from press releases and a few abstracts presented at scientific meetings. In short-term controlled trials, it was more effective than placebo in reducing positive and negative symptoms of schizophrenia, with an effective dose range of 1.5–12 mg/day. Although cariprazine was associated with a higher incidence of akathisia and extrapyramidal side effects than placebo, it did not cause weight gain, metabolic abnormalities, prolactin increase, or corrected QT prolongation. Similarly, cariprazine's efficacy and tolerability for the treatment of bipolar disorder (manic/mixed and depressive episodes) was established in the dose range of 3–12 mg/day, although again no long-term data are available. Well-designed clinical trials, mainly direct "head-to-head" comparisons with other second-generation antipsychotic agents, are needed to define the therapeutic role and safety profile of cariprazine in schizophrenia and bipolar mania. Keywords: cariprazine, antipsychotic, pharmacology, pharmacokinetics, efficacy, safety